Effect of Smoking and Noise Exposure on Hearing Threshold Levels in Industrial Workers in West of Iran - Behzad Fouladi Dehaghi; Abbas Mohammadi; Leila Ibrahimi Ghavamabadi; Ghasem Mardi; Amel Saki (Iranian Journal of Health, Safety and Environment, 2019)
Cigarette smoking had many adverse effects on health, also exposure to industrial noise is known as a health risk factor in the workplaces. The aim of this study was to investigate the relationship between industrial noise exposure and smoking on the hearing threshold levels in workers. In the study, 200 male workers in the two groups (100 smokers and 100 nonsmokers with noise exposure) were involved. To assess noise exposure used calibrated noise dosimeter. Demographic, smoking habits and health status information was obtained via questionnaire. The results showed a significant difference between noise-induced hearing loss (NIHL) in two ears and total NIHL in smokers and non-smokers with less than 10 years and more 10 years of noise exposure duration. From the outcome of this investigation it is possible to conclude a positive effect between cigarette smoking and noise exposure on hearing loss and it can be suggested that hearing protection programs should train workers about the increased risk of developing NIHL from smoking and exposure to high occupational noise levels.